Kecepatan Laju Reproduksi Vegetatif berbagai Jenis Bambu di PPKA Bodogol, Taman Nasional Gunung Gede Pangrango - Sulistyowati, Syifa Eka; Marmy, Dita Ervianti, Maulidia A.R.; Andria, Rani F.; Fauziah, Risna (Bioma, 2014)
Abstract Bamboo spread naturally in tropical and subtropical regions of all continents except Europe, found at altitudes of up to 4000 meters above sea level. In the rainy season bamboo will experience growth of stems or bamboo shoot can grow 70% maximum height and diameter. The purpose of this research was to determine the rate of growth of bamboo in PPKA Bodogol, Gunung Gede Pangrango National Park. The result found 8 types of bamboo, there were Schizostachyum bamban, Gigantochloa pseudoarundinacea, Dinochloa scandens, Bambusa vulgaris, Gigantochloa apus, Gigantochloa atter, Gigantochloa hasskarliana, and Gigantochloa sp. The growth rate all of species is 13,49 cm/ day. From some types of bamboo, the growth were above average and was found on the Schizostachyum bamban, Gigantochloa sp.. The Species with fastest growth is Gigantochloa sp and the longest is Gigantochloa apus. Key words: bamboo, bamboo shoot, Gigantochloa, the rate of growth